Analyzing the Growing Needs of Users to Employ Hardware and Software Restrictions in Smartphones for Increased Privacy and Data Security - Philip, Jithu; Raju, Merin (Indian Journal of Computer Science, 2021)
The use of smartphones has become an inevitable part of the lives of common people, as these days almost every day to day activity requires the active use of smartphones for the real world task processing. As the demanding needs of smartphones with the bundled operating system code along with a huge variety of user applications increased, there also exists an evil part hidden within the wide variety of applications that the application developers make use of to gain profit by collecting details about users either as private personal documents or in the form of metadata. As normal users of the system, they may not be always informed or well known about the ways in which these applications work. There also exists a problem where user security is compromised in the form of malicious code. Many government organizations collect and record information about user activity through telecom operators in the name of some backdoor operations they were working without the user’s consent. In this paper we try to focus on the perspectives that a common user needs to be aware of, to make their system more private and secure it from data breeches.